Accelerated two-year degrees in the UK: potential impact on student mental health. Issue 1 (3rd October 2019) - Hack-Polay, Dieu; Read, Magdalena
Abstract : Purpose: The purpose of this paper is to examine the ramifications of accelerated two-year degrees for student mental health. Since it was legislated in early 2019 in the UK, there has been limited debate in academia and among policymakers about the potential viability and risks of the compressed degree programmes. Design/methodology/approach: The paper is based on an analysis of various academic and practitioner viewpoints as well as theoretical perspectives. Findings: The paper found a mixed reception of the compressed degree programme among the academic and practitioner communities. In addition to apprehensions about the quality of education, there are concerns raised about the impact of the pressure deriving from the workload of the accelerated degree. The authors' assessment considers a potential increase in stress and other more acute state of mental health degradation among students, especially international students, as well as students with families. Originality/value: This policy analysis paper makes a significant contribution to the debate on the issue of two-year degrees that has not attracted academic scrutiny commensurate with its importance. The authors conclude that two-year degrees will have far-reaching ramifications, locally and internationally as the UK continues to push for its widening participation agenda as well as maintain its position as one of the top three destinations for international students. The authors suggest that wider discussions with stakeholder and some impact studies are needed before the accelerated degrees are further popularised in universities.